2019
DOI: 10.1002/chem.201902887
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Saturated Red Light‐Emitting Electrochemical Cells Based on Cationic Iridium(III) Complexes with EQE up to 9.4 %

Abstract: Solid‐state light‐emitting electrochemical cells (LECs) have several advantages, such as low‐voltage operation, compatibility with inert metal electrodes, large‐area flexible substrates, and simple solution‐processable device architectures. However, most of the studies on saturated red LECs show low or moderate device efficiencies (external quantum efficiency (EQE) <3.3 %). In this work, we demonstrate a series of five red‐emitting cationic iridium complexes (RED1‐‐RED5) with 2,2′‐biquinoline ligands and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
1
22
1
Order By: Relevance
“…Most important of all, the phosphorescent nature of iTMCs commonly results in more efficient electroluminescence (EL) than other fluorescent materials. Some LECs employing efficient iTMCs were reported to achieve similar device performance to that published for OLEDs. In addition to efficient emissive materials, optimizing the carrier balance, that is, balancing the number of electrons and holes, of LECs is critical to take full advantage of efficient emissive materials. Several device engineering methods to improve the balance of carrier transport, for example, carrier trapping or blocking, adjusting carrier injection, salt incorporation, modifying carrier transporting, emissive-layer thickness optimization, and optimizing emission zone position ,, were shown for improving the device performance of LECs .…”
Section: Introductionmentioning
confidence: 89%
“…Most important of all, the phosphorescent nature of iTMCs commonly results in more efficient electroluminescence (EL) than other fluorescent materials. Some LECs employing efficient iTMCs were reported to achieve similar device performance to that published for OLEDs. In addition to efficient emissive materials, optimizing the carrier balance, that is, balancing the number of electrons and holes, of LECs is critical to take full advantage of efficient emissive materials. Several device engineering methods to improve the balance of carrier transport, for example, carrier trapping or blocking, adjusting carrier injection, salt incorporation, modifying carrier transporting, emissive-layer thickness optimization, and optimizing emission zone position ,, were shown for improving the device performance of LECs .…”
Section: Introductionmentioning
confidence: 89%
“…Several LECs based on efficient iTMCs have been reported to achieve comparable device efficiencies to those measured for OLEDs [19–25] . However, most high‐efficiency iTMCs are blue, [22–24] green, [19, 20] and yellow, [25] whereas the reported red iTMCs commonly show lower photoluminescence quantum yields, [26–29] which limit further enhancement of the device efficiency of host–guest white LECs based on iTMCs. Recently, incorporation of efficient QDs in LECs [30–32] has inspired the idea of the hybrid white LECs combining a yellow iTMC and blue QDs [33] .…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Accordingly, it was shown that the increasing of the hydrophobicity of the active layer by introducing the hydrophobic side group and the formation of a supramolecular cage by intramolecular face-to-face π-π stacking interactions in the structure of the emitter can also be effective in preventing nucleophiles from gaining access to the metal center, thus leading to more desirable device stability. [32][33][34][35][36][37][38] Another way to increase the stability of LECs is to increase the number of metal centers. 39 Therefore, the use of multi-nuclear complexes can be a convenient method to increase the stability of devices.…”
Section: Introductionmentioning
confidence: 99%